What is the “usefulness” of pibid psychology? - Longo, Cristiano da Silveira; Narita, Stella (Revista Hipótese, 2016)
This study presents and discusses the possibilities of a psychology project within the Institutional Scholarship Program for Teacher Initiation (PIBID), as a part of PIBID’s Institutional Project at the Federal University of Grande Dourados (UFGD). From a methodological standpoint, it proposes the development of operative group activities in teaching, addressing transversal themes such as ethics, cultural plurality, health, sexuality, work, consumption and professional guidance. Upon reflection on the usefulness of a project of this nature, it concludes that it is necessary to face the so-called “urgent social issues”, often relegated to a secondary role in the formal curricular design and in everyday school practices.
Keywords: PIBID; Teacher education; Teacher licensing; Psychology; Operative group